2014
DOI: 10.5455/gmj-30-43192
|View full text |Cite
|
Sign up to set email alerts
|

Anti-retroviral therapy adherence and its determinants among adult patients living with HIV/AIDS in South West Ethiopia: a facility-based cross sectional study

Abstract: Adherence to anti-retroviral therapy (ART) regimen is essential for successful treatment and sustained viral control. Optimal adherence is the compliance to ART that achieves a sustained plasma drug concentration that suppresses viral replication. The objective of this study is to assess ART adherence and its determinants at Agaro Health Center ART Clinic, South Western Ethiopia. Facility-based cross sectional study was conducted from June 9-29, 2011. Patients were interviewed to collect adherence related info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
5
4
1
Order By: Relevance
“…This was much lower than our result con-firming that patients in developing countries can achieve good adherence despite limited resources. Study conducted in South West Ethiopia indicated that level of adherence was 98.8%, which is higher than that we found [17].…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…This was much lower than our result con-firming that patients in developing countries can achieve good adherence despite limited resources. Study conducted in South West Ethiopia indicated that level of adherence was 98.8%, which is higher than that we found [17].…”
Section: Discussioncontrasting
confidence: 84%
“…In our study, we found that females were more adhered than males. Study done in South Western Ethiopia also indicated that females were more adhered than males [17]. The resulting higher rate of increase in the medication adherence for females than males might be attributed to females believes in self efficacy in whatever they do in order to succeed.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…6 Out of literate respondents majority 28 (35.9%) were primary level similar to study done at West Ethoipia by Ejigu. 8 Majority of respondents 155 (98.9%) were employed and similar finding is present in India. [7] Out of employed respondents majority 71 (45.8%) were housewife, similar to the study done at West Ethiopia by Ejigu.…”
Section: Discussionsupporting
confidence: 60%
“…[7] Out of employed respondents majority 71 (45.8%) were housewife, similar to the study done at West Ethiopia by Ejigu. 8 Majority of the respondents 125 (78.1%) have family history of HIV and have family history of ART 98 (78.4%), as contradictory findings are reported in West Bengal, India. 7 Majority of the respondents 53 (33.1%) were diagnosed HIV for more than 6 years back followed by 44 (27.5%) before 4-6 years, 38 (23.8%) before 2-4 years and 25 (15.6%) before 2 years whereas findings are in contrast as reported by Bam. 5 Majority of the respondents 71 (44.1%) receive combined ART regimen of Zidovudine, Lamivudine and Nevirapine (AZT/3TC/NVP) similar to the study reported by Saha.…”
Section: Discussionmentioning
confidence: 70%